Flavonoids extracted from orange peelings tangelo (Citrus reticulata x Citrus paradisi) and their application as a natural antioxidant in sacha inchi (Plukenetia volubilis) vegetable oil - Tenorio-Domínguez, Matilde (2016)
The purpose of this research was to obtain extracts of flavonoids from orange tangelo peelings (Citrus reticulata x Citrus paradisi) and apply them as natural antioxidant to the vegetable oil Sacha inchi (Plukenetia volubilis). The information was obtained from experimental tests which were made in seven steps: physical and chemical characterization of the orange tangelo and the sacha inchi oil; extraction of flavonoids by the Soxhlet extractor; detection of flavonoids in each extract through fine layer chromatography and paper chromatography; identification and quantification of flavonoids by high resolution chromatography liquid (HPLC); determination of the antioxidant capacity of each extract of flavonoid, and finally evaluation of the antioxidant activity in oil sacha inchi, of the extract with the higher level of antioxidant capacity using a multifactorial design with two factors: extracts of flavonoids and concentration at three levels: 0.05%; 0.1% and 0.15%, and 16 blocks which are the times. The results showed that the liquid extract had the greatest quantity of flavonoids: 100.3724 mg/g, being naringine with 81.1727 mg/g, the flavonoid found in greatest proportion. At a concentration of 0.1%, the extract of flavonoid showed the lowest index of peroxide at 384 hours. It is concluded that the flavonoids present in the orange tangelo peeling can be used as raw extracts, without needing partial or total purification, to increase the sacha inchi oil life.